10 When is it time to switch the ICD off in a heart failure patient?. (24th April 2019) - Cheung, Lily
Abstract : It is well documented that implantable cardioverter defibrillator (ICD) saves lives in populations at risk for sudden death. However, mortality in advanced heart failure remains high despite advances in therapy. 1 Twenty per cent of ICD patients receiving shocks in the final weeks of their lives experience pain and decreased quality of life, causing distress to patients and their families. 2 Ethically and legally, there are no differences between refusing ICD therapy and requesting withdrawal of ICD therapy. Carrying out a request to withdraw life-sustaining treatment is neither physician-assisted suicide nor euthanasia. 3 Decisions about deactivation of ICD are complicated. Proactive communication by clinicians before implant and during device follow-up are important in order to minimise suffering as the end of life nears for patients with ICDs. Clear discussion about the benefits and burdens of the device should be made. Advance care planning addressing device deactivation should be encouraged for all patients with ICD. 4 References: Goldberger Z, Lampert R. Implantable Cardioverter-defibrillators: expanding indications and technologies. JAMA 2006;295;809–818 Goldstein NE, Lampert R, Bradley E, Lynn J, Krumholz HM. Management of implantable cardioverter defibrillators in end-of-life care. Ann Intern Med 2004;141:835–838. Lampert R, Hayes DL, Annas GJ, Farley MA, Goldstein NE, Hamilton RM, Kay GN, Kramer DB, Mueller PS, Padeletti L, Pozuelo L, Schoenfeld MH, Vardas PE, Wiegand DL, Zellner R; American College of Cardiology; American Geriatrics Society; American Academy of Hospice and Palliative Medicine; American Heart Association; European Heart Rhythm Association; Hospice and Palliative Nurses Association. HRS Expert Consensus Statement on the Management of Cardiovascular Implantable Electronic Devices (CIEDs) in patients nearing end of life or requesting withdrawal of therapy. Heart Rhythm 2010;7:1008–1026. BHF. ICD deactivation at the end of life: Principles and practice. 2013. https://www.bhf.org.uk/-/media/files/publications/hcps/icd-deactivation.pdf